THE EFFECTIVENESS OF PREGNANT WOMEN CLASS TO INCREASE KNOWLEDGE AND HEMOGLOBIN LEVEL - Husna, Putri Halimu; Purwandari, Kristiana Puji; Mawarni, Siti; Sundari, Sri; Wardani, Indah Kusuma; Maryati, Maryati (Journal of Maternal and Child Health, 2020)
Background: Intrauterine Fetal Death (IUFD) is a birth process of a conception result in a state of death. It is also a contributor to death for Infant Mortality Rate (IMR). Pregnant Woman Class is a government effort to reduce IMR. However, the implementation has not been maximized. This study aimed to determine the effectiveness of pregnant woman class in increasing the level of knowledge and hemoglobin (Hb) levels of the pregnant woman.Subjects and Method: This was a Randomized Controlled Trial (RCT). The population of the study consisted of 170 pregnant women was selected randomly from 3 Community Health Centers with the highest infant mortality rates. The dependent variables were knowledge and Hb levels. The independent variable was pregnant woman class. The level of knowledge was measured by questionnaire with Cronbach's alpha by 0.64. Hb level was measured with Easy Touch GCHB. The Mean differences in knowledge and Hb between pregnant women class and control groups, before and after participating in pregnant woman class, were tested by independent t-tests.Results: Before the intervention, the level of knowledge of the pregnant women class group (Mean= 31.07; SD=8.21) was comparable with the control group (Mean=29.30; SD=8.22), with p=0.162. It indicated the randomization success. After the intervention, the level of knowledge of pregnant woman class group (Mean=35.07; SD=2.24) was higher than the control group (Mean= 29.10; SD= 4.77), and it was statistically significant (p<0.001). It indicated that the pregnant woman class was effective in increasing the knowledge of pregnant women. Before the intervention, the Hb level of pregnant woman class group (Mean=11.92, SD=2.18) was comparable with the control group (Mean= 11.44; SD= 2.05), with p=0.162. It indicated the randomization success. After the intervention, the Hb level of the pregnant woman class group (Mean = 12.82; SD = 0.92) was higher than the control group (Mean=11.56; SD=1.05), and it was statistically significant (p<0.001). It showed that pregnant woman class was effective in increasing the Hb level of pregnant women.Conclusion: Pregnant woman class was effective in increasing the knowledge and the Hb level of pregnant women.Keywords: pregnant woman class, knowledge, hemoglobin, IUFDCorrespondence: Putri Halimu Husna. Nursing Academy of Giri Satria Husada Wonogiri. Jl. Tentara Pelajar 01 Giriwono, Wonogiri 57613, Central Java. Email: ns.haha354@gmail.com. Mobile: +62273322610, +6281391277044.Journal of Maternal and Child Health (2020), 5(1): 50-57https://doi.org/10.26911/thejmch.2020.05.01.06